The relationship between gut microbiome and human diseases: mechanisms, predisposing factors and potential intervention - Shabani, Mohammad; Ghoshehy, Ali; Mottaghi, Amir Mohammad; Chegini, Zahra; Kerami, Azam; Shariati, Aref; Taati Moghadam, Majid (Frontiers in Cellular and Infection Microbiology, 2025)
The complex interrelation of gut microbiota with human health underlines the profound influence this microbial ecosystem has on mechanisms of disease and wellness. The gut microbiome profoundly impacts various human diseases, encompassing gastrointestinal disorders, metabolic disorders, neurological disorders, and immune-related diseases. Gastrointestinal disorders are closely linked to microbial imbalances in the gut. Metabolic disorders, including obesity and type 2 diabetes, are influenced by the gut microbiota’s role in energy regulation and glucose metabolism. Furthermore, the gut-brain axis highlights the correlation between gut microbiota and neurological conditions such as Alzheimer’s and Parkinson’s. Moreover, the gut microbiome assumes a pivotal function in regulating the immune system, whereby dysbiosis is implicated in developing immunological-related ailments, including allergies and autoimmune disorders. Predisposing factors, including diet, medicines, lifestyle, and environmental influences, are described as having an important role in the composition of the gut microbiome. By understanding these factors, we can get valuable insights into how to intervene to reduce the chances of a disease. Current interventions, including probiotics, prebiotics, fecal microbiota transplants, and lifestyle modification, show promise, but there are still challenges and unanswered questions in this evolving field that may lead to improvements. This review interrelates the complicated gut microbiome with various human diseases, mechanisms, predisposing factors, and potential interventions.